Development and Validation of the Standard Chinese Version of the CARE Item Set (CARE-C) for Stroke Patients. Issue 42 (October 2015) - Chang, Ke-Vin; Hung, Chen-Yu; Kao, Chien-Wei; Tan, Fuk-Tang; Gage, Barbara; Hsieh, Ching-Lin; Wang, Tyng-Guey; Han, Der-Sheng
Abstract : Abstract: The Continuity Assessment Record and Evaluation (CARE) item set is a standardized, integrative scale for evaluation of functional status across acute and postacute care (PAC) providers. The aim of this study was to develop a Chinese version of the CARE (CARE-C) item set and to examine its reliability and validity for assessment of functional outcomes among stroke patients. The CARE-C was administered in two samples. Sample 1 included 30 stroke patients in the outpatient clinic setting for the purpose of examining interrater and test–retest reliabilities and internal consistency. Sample 2 included 138 stroke patients admitted to rehabilitation units for the purpose of investigating criterion-related validity with the Barthel index, Lawton Instrumental Activities of Daily Living (IADL) scale, EuroQOL five dimensions questionnaire (EQ-5D), and Mini-Mental State Examination (MMSE). The CARE-C was categorized into 11 subscales, 52 items of which were analyzed. At the subscale level, the interrater reliability and test–retest reliability expressed by intraclass correlation coefficient (ICC) ranged from 0.72 to 0.99 and 0.60 to 1.00, respectively. Six of the 11 subscales met acceptable levels of internal consistency (Cronbach alpha > 0.7). The criterion-related validity of the CARE-C showed moderate to high correlations of its subscales of cognition and basic and instrumental activities of daily living with the Barthel index, IADL scale, and MMSE. The CARE-C is a useful instrument for evaluating functional quality metrics in the Chinese stroke population. The development of the CARE-C also facilitates the assessment of the PAC program in Taiwan and future research is warranted for validating the capability of CARE-C to identify patients' functional change over time and its generalizability for nonstroke populations.